Analisis Tekanan Penduduk dan Daya Dukung Lahan Padi Gogo di Kecamatan Mustikajaya Kota Bekasi - M. Deni Rachmansyah; Titik Ekowati; Wahyu Dyah Prastiwi (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2022)
This study aimed to analyse the population pressure and the carrying capacity of agricultural land (upland rice). The benefit of the research was to provide information for young farmers as a form of consideration for clearing agricultural land from the income used by the population. The research was carried out from September-November Year of 2021 in The District of Mustikajaya, Bekasi City. This research used descriptive quantitative approach with a survey method. Determination of the location was based on the need for high managed land and conversion of upland rice. Types of research data in the form of primary data and secondary data. Data collection methods included interviews, documentation, and literature study. The sampling method was a proportional sampling method. Analysis of the data in this study is Analysis of Population Pressure Index (PPI) and Analysis of Carrying Capacity Land (CCL). The results showed that the PPI value in The District of Mustikajaya was 1.55 people/ha and the CCL value for Upland Rice was 0.65 ha. The conclusions of the study are 1) Population pressure in The District of Mustikajaya has exceeded the threshold for agricultural land; 2) The carrying capacity of upland rice fields in The District of Mustikajaya is low.